Role of Teacher Education in the Achievement of MDGs - Amardeep Kaur; Kulwinder Singh (International Journal of Evaluation and Research in Education (IJERE), 2014)
The Millennium Development Goals (MDGs) which include eight goals have been framed to address the world's major development challenges by 2015. In India, considerable progress has been reported to be made in the field of basic universal education, gender equality in education, economic growth and other human development related aspects. Even though the government has implemented a wide array of programmes, policies, and various schemes to combat these challenges, further intensification of efforts and redesigning of outreach strategies are needed to give momentum to the progress toward achievement of the MDG-2 (Achieve Universal Primary Education) and MDG-3 (Promote Gender Equality).To universalize elementary education, Sarva Shiksha Abhiyan (SSA) is one of the major schemes introduced by the government in 2002. Education Guarantee Scheme (EGS) and Alternative and Innovative Education are the components of SSA. Universal enrolment is one of the specific objectives of SSA. The strategy of implementation of Mid-Day Meal Scheme has also played a role in enhancing the enrolment and retention of the students. To focus on girls’ education, several schemes have been incorporated within SSA. National Programmes for Education of Girls at Elementary Level (NPEGEL) and Kasturba Gandhi Balika Vidyalaya Scheme (KGBVS) focus on primary education for girls. In order to achieve this, there is need to ensure sufficient number of schools along with adequately trained teachers for quality instruction and effective functioning of primary education programmes. This is more true in the context of RTE- 2009. Achieving universal schooling requires cent percent enrolment and it also means ensuring that all children continue to attend classes till completion of eight years of schooling (6-14 years) in the near future. Education benefits not only at the individual level but also for the development of country as a whole.  Further gender inequality in education has a direct impact on economic growth through lower levels of quality of human capital. In the light of these emergent issues in school education there is need to develop a sense of higher levels of commitment and sincerity among the prospective teachers. The teacher education programmes need to be reoriented to look into the issues related to enrolment and retention of children along with ensuring quality inputs in teaching -learning process. Hence an effort has been made to address to these issues in school education for the effective designing of on-going teacher education programmes to enable the prospective teachers as well as those in schools for effective implementation of different interventionistic programmes.DOI: http://dx.doi.org/10.11591/ijere.v3i2.5652